Iron overload after allogeneic stem cell transplantation in children with acute lymphoblastic leukemia. (27th October 2020) - Salmi, Asta; Holmström, Miia; Toiviainen‐Salo, Sanna; Kanerva, Jukka; Taskinen, Mervi
Abstract: Red blood cell transfusions are an essential part of supporting care in leukemia treatment. We examined the prevalence of iron overload and its effects on organ function and childhood growth in pediatric patients after allogeneic HSCT for acute lymphoblastic leukemia. Twenty‐three patients were included (median age 12.6, range 7.5‐21.4 years). Body iron load was determined using laboratory tests, hepatic and cardiac MRI, and by calculating iron received from transfusions. We performed multivariate analysis to determine association of body iron load with liver enzymes, cardiac function, insulin resistance, and growth. Median plasma ferritin was 344 (range 40‐3235) ng/mL and exceeded 1000 ng/mL in three patients (13%). In MRI, 11 patients (48%) had hepatic iron overload and 1 patient (4%) myocardial iron overload. In cardiac MRI, 8 patients (35%) had significant but subclinical decrease in ejection fraction (median z‐score −1.7, range −3.1‐0.14), but cardiac function did not associate with iron status. Alanine transaminase associated with transfused iron per time unit ( P  = .001) after the median follow‐up of 4.5 years. No correlation was found between iron load and growth or insulin resistance. Iron overload is common in children transplanted for ALL, but iron overload associated organ dysfunction is not present at early age. We recommend evaluation of iron load for all patients at least once during follow‐up after transplantation.